Comunidades profesionales de aprendizaje en un contexto remoto por la emergencia sanitaria - Rivera Huaranga, Nancy Edith (2021)
The objective of the study was to determine the differences that exist in the factors that describe the Professional Learning Communities in the Educational Institutions of East Lima in a context of remote work due to the health emergency, according to educational level, sex, age and academic training. We worked from a quantitative approach and a comparative descriptive design. The study sample consisted of 144 teachers from East Lima, to whom the questionnaire adapted and validated by Bolívar (2017): Evaluation of Professional Learning Communities, was applied virtually. The analysis carried out on the basis of the statistical data allowed to establish the differences at the level of the dimensions of the Professional Learning Communities; The research shows that the factors that involve the Professional Learning Communities in the Educational Institutions of East Lima, prevail a level of regular higher than 50%, in the dimensions of shared leadership and support, shared vision and values, collective learning and application, shared professional practice, support conditions: relationships and support conditions: structure; followed by the efficient level; likewise, in all dimensions greater than 27.1%; Therefore, it can be said that the professional communities under study have been adequately managed by the actors under study.